Natural and artificial dyes: its health risks - Morais Antonini, Luana (Seven Editora, 2023)
The aim of this study was to research the use of food dyes and their risks to human health. Its methodology was descriptive bibliographic review. Based on the survey, it is verified that although natural dyes are the most indicated, artificial ones are the most used by the food industry because they have high stability, uniformity in the color conferred, high tintorial power, exemption from microbiological contamination and relatively low production cost. DOI: https://doi.org/10.56238/tfisdwv1-069